ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI TINGKAT KEPARAHAN KEMISKINAN DI PROVINSI SUMATERA BARAT Hatika Marreza, Idris - Hatika Marezza; idris Idris (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
: This study aims to analyze the effect of factor (X1) cigarette consumption toward the severity of poverty, (X2) education toward the severity of poverty, (X3) health toward the severity of poverty, in West Sumatra. This study uses data analysis methods which uses multiple linear analysis using the Ordinary Least Square approach. This study uses the Susenas data of West Sumatra Province in 2017. The results of the study show that (1) Cigarette consumption does not have a significant effect toward poverty severity. (2) Education has a significant effect toward the severity of poverty. (3) Health does not have a significant effect toward the severity of poverty. (4) Taken together there is a significant influence between Cigarette Consumption, Education and Health toward the severity of poverty in West Sumatra. Therefore, it is expected that the public can reduce cigarette consumption to reduce the severity of poverty. For education, the government is expected to try to pay attention to and improve the development of decent infrastructure with more teaching staff. Health needs to be improved so that health complaints are reduced so as to support production activities and the maximum income earned and poverty will decrease.for further research on the analysis of factors that influence the severity of poverty can be added with other variables to be more complete.